Diagnosing Meniscal Pathology and Understanding How to Evaluate a Postoperative Meniscus Based on the Operative Procedure - Tafur, Monica; Probyn, Linda; Chahal, Jaskarndip; White, Lawrence M. (The Journal of Knee Surgery, 2018)
Magnetic resonance imaging (MRI) represents the preferred noninvasive imaging technique to diagnose meniscal pathology in the pre- and postoperative setting. Furthermore, characterization of meniscal tissue MR properties has been possible by the development of advanced MRI techniques. Suspected meniscal tears are a frequent indication for MRI and the International Society of Arthroscopy, Knee Surgery and Orthopaedic Sports Medicine (ISAKOS) classification system has been developed to facilitate accurate and uniform reporting of such meniscal tears. Partial meniscectomy and meniscal suture repair are among the commonly performed procedures and several signs have been described to detect postoperative recurrent tears on MRI. Other techniques that have proven useful for meniscal assessment are ultrasound (US) and computed tomography (CT) arthrography. In recent years, US is being increasingly used in the selective assessment of some meniscal pathology such as tears, parameniscal cysts and meniscal extrusion as it is a relatively inexpensive, accessible, and safe technique. CT arthrography has been advocated as an acceptable alternative in patients with contraindications for MRI, with comparable diagnostic performance.
Keywords: magnetic resonance imaging; ultrasound; meniscus; meniscal tears; postoperative